PENGAMBILAN KEPUTUSAN OVERHAUL DAN REPAIR PADA PERAWATAN MESIN PRODUKSI - Kurniawan, Fajar; Hartono, Gunawarman (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
If an Â industry Â wants to get product out put with competitive high quality, price, and time precise, it must be able to efficient the production process. One of way to reach it is by improving the utilize of tools and engine. That will come true if it supported by a good nursery management so it can produce a supportive decision of production activity and minimize the down time.